Interfacial Electrochemistry - Schmickler, Wolfgang; Santos, Elizabeth; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Electrochemistry is an old branch of physical chemistry. Due to the development of surface sensitive techniques, and a technological interest in fuel cells and batteries, it has recently undergone a rapid development. This textbook treats the field from a modern, atomistic point of view while integrating the older, macroscopic concepts. The increasing role of theory is reflected in the presentation of the basic ideas in a way that should appeal to experimentalists and theorists alike. Special care is taken to make the subject comprehensible to scientists from neighboring disciplines, especially from surface science. The book is suitable for an advanced course at the master or Ph.D. level, but should also be useful for practicing electrochemists, as well as to any scientist who wants to understand modern electrochemistry.
Metal and semiconductor electrodes -- Electrolyte solutions -- A few basic concepts -- The metal-solution interface -- Adsorption on metal electrodes: principles -- Adsorption on metal electrodes: examples -- Thermodynamics of ideal polarizable interfaces -- Phenomenological treatment of electron-transfer reactions -- Theoretical considerations of electron-transfer reactions -- The semiconductor-electrolyte interface -- Selected experimental results for electron-transfer reactions -- Inner sphere and ion-transfer reactions -- Hydrogen reaction and electrocatalysis -- Metal deposition and dissolution -- Electrochemical surface processes -- Complex reactions -- Liquid?liquid interfaces -- Experimental techniques for electrode kinetics – non-stationary methods -- Convection techniques.
Keywords: Electrochemistry; Materials—Surfaces.; Thin films; Energy storage; Electrochemistry; Surfaces and Interfaces, Thin Films; Energy Storage